2016
DOI: 10.23861/ejbm20132929
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of an Implantable Cardioverter-Defibrillator: A Qualitative Study of Families with a History of Sudden, Life-Threatening Cardiac Events, and Recommendations to Improve Care

Abstract: Results: Participants reported concerns about ICDs, and these concerns were categorized into six themes: (1) comprehension and physician-patient communication; (2) anxiety; (3) restrictions and fallacies; (4) complications; (5) utility; and (6) alternative therapy. Participants noted communication breakdowns between providers and their colleagues, and between providers and their patients. Participants and their families experienced many different forms of anxiety, including worry about the aesthetics of the IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Erskine et al (2013) described the advantages of an interdisciplinary approach for personalized medicine. Linder et al (2013) identified major concerns associated with ICD implantation. The entire data set is available from the corresponding author.…”
Section: A General Populationmentioning
confidence: 99%
“…Erskine et al (2013) described the advantages of an interdisciplinary approach for personalized medicine. Linder et al (2013) identified major concerns associated with ICD implantation. The entire data set is available from the corresponding author.…”
Section: A General Populationmentioning
confidence: 99%
“…[ 6 ] Therefore, patients living with ICD experience a high rate of insomnia,[ 7 ] depression and anxiety,[ 8 ] and stress. [ 9 ] Furthermore, patients after ICD placement may show fear,[ 10 ] feelings of loneliness and lack of support,[ 11 ] self-restrictions on physical activity,[ 12 ]feeling of an involuntary job move,[ 13 ] worries about their future,[ 14 ] communication restrictions,[ 15 ] and the unpleasant feeling when the shock is discharged. [ 16 ] However, the occurrence of mood disorders is a risk factor for CVD, recurrence of cardiac events,[ 9 ] and non-adherence to treatment.…”
Section: Introductionmentioning
confidence: 99%
“… Published reports that have analyzed different themes from this research team include: Barlevy et al , who addressed reproductive decision-making in the context of genetic predispositions to sudden cardiac death [18]; Cohen et al , who discussed special considerations for genetic testing with adolescents [19]; Erskine et al , who described the advantages of an interdisciplinary approach to personalized medicine [20]; Linder et al , who identified major concerns associated with an implantable cardioverter-defibrillator (ICD) [21]; and Erskine et al , who analyzed motivations to pursue genetic testing in individuals with a personal or family history of cardiac events or sudden cardiac death [22]. The entire data set is available from the corresponding author.…”
mentioning
confidence: 99%